2000
DOI: 10.1073/pnas.020510097
|View full text |Cite
|
Sign up to set email alerts
|

High relatedness and inbreeding at the origin of eusociality in gall-inducing thrips

Abstract: A ustralian gall-inducing thrips gain food and shelter, in the form of a gall, from species of Acacia trees (1-6). The gall is formed as a female feeds on a developing phyllode (a petiole modified to serve as a stem and leaf) that encapsulates her and in some cases a male (4, 6). The foundress oviposits within the gall, and the developing thrips feed by sucking out the contents of plant cells on the gall's inner wall (1). In eusocial species, the first cohort to eclose are gall-bound soldiers, which are distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 30 publications
1
70
0
1
Order By: Relevance
“…In contrast to Hymenoptera, in eusocial haplodiploid thrips both male and female offspring participate in nest defense (Crespi 1992;Kranz et al 1999). The evolution of both male and female helpers in eusocial thrips may be linked to lack of pre-adapations in either sex to soldiering, as suggested by Ross et al (2013), but also to the high degree of ancestral inbreeding in these species (McLeish et al 2006), which reduces the importance of relatedness asymmetries (Chapman et al 2000). For diplodiploid species, our model predicts equal benefit thresholds for males and females.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to Hymenoptera, in eusocial haplodiploid thrips both male and female offspring participate in nest defense (Crespi 1992;Kranz et al 1999). The evolution of both male and female helpers in eusocial thrips may be linked to lack of pre-adapations in either sex to soldiering, as suggested by Ross et al (2013), but also to the high degree of ancestral inbreeding in these species (McLeish et al 2006), which reduces the importance of relatedness asymmetries (Chapman et al 2000). For diplodiploid species, our model predicts equal benefit thresholds for males and females.…”
Section: Discussionmentioning
confidence: 93%
“…Against this hypothesis, Hughes et al (2008) showed that monogamy-which maximizes relatedness of offspring-was ancestral in all eight Hymenopteran lineages that evolved eusociality. An important role for kin structure is also supported by the association of sociality with inbreeding in certain thrips (Chapman et al 2000) and spiders (Agnarsson et al 2006). Sponge-dwelling shrimp provide an independent test of the role of kin structure in the origin of eusociality.…”
Section: Discussionmentioning
confidence: 99%
“…Second, does group living indeed confer ecological advantages in enhancing ability to acquire and defend limited territories or other resources? Despite a long history of research, surprisingly few formal comparative studies have tested the importance of either genetic relatedness (but see Chapman et al 2000;Agnarsson et al 2006;Hughes et al 2008) or the hypothesized ecological benefits of social life in groups near the origin of eusociality. This is due in part to the generally ancient origins and phylogenetic conservatism of eusocial life in the major lineages of social insects, which obscure the conditions associated with the origins of eusociality (Crespi 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Crespi (1992b) suggested that the evolution of eusociality in thrips may have been associated with haplodiploidy, but phylogenetic studies show that high levels of inbreeding were present at the origin of eusociality in thrips, and the effect of inbreeding is likely to overwhelm the effect of haplodiploidy in lowering thresholds for altruistic behaviour (Chapman and Crespi, 1998;Chapman et al, 2000). Apart from eusociality, thrips have importance for evolutionary studies because of a number of other traits that are relevant to understanding the evolution of life history strategies (Kranz, 2000).…”
Section: Introductionmentioning
confidence: 99%